2005
DOI: 10.1128/jvi.79.10.6194-6206.2005
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl-Proximal Regions of Reovirus Nonstructural Protein μNS Necessary and Sufficient for Forming Factory-Like Inclusions

Abstract: Mammalian orthoreoviruses are believed to replicate in distinctive, cytoplasmic inclusion bodies, commonly called viral factories or viroplasms. The viral nonstructural protein NS has been implicated in forming the matrix of these structures, as well as in recruiting other components to them for putative roles in genome replication and particle assembly. In this study, we sought to identify the regions of NS that are involved in forming factory-like inclusions in transfected cells in the absence of infection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
113
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(116 citation statements)
references
References 46 publications
(113 reference statements)
3
113
0
Order By: Relevance
“…Specific regions within the NS protein that are required for recruitment of the viral core and six other MRV proteins to VFs and for forming VFs have previously been identified (6,7,9,10,12) (Fig. 1A).…”
Section: Construction Of Plasmids Expressing the Tc Tag From Within Tmentioning
confidence: 99%
See 4 more Smart Citations
“…Specific regions within the NS protein that are required for recruitment of the viral core and six other MRV proteins to VFs and for forming VFs have previously been identified (6,7,9,10,12) (Fig. 1A).…”
Section: Construction Of Plasmids Expressing the Tc Tag From Within Tmentioning
confidence: 99%
“…We separated the TC-NS mutants based on previously identified functions of NS to include the N-terminal third (aa 1 to 221), the central third (aa 222 to 470), and the C-terminal third (aa 471 to 721). Previous studies have found that the NS N-terminal third is both necessary and sufficient to bind virus proteins NS, 2, 1, 2, and 2, the C-terminal third is necessary and sufficient to bind 3, form VFs, and bind cellular clathrin, and the central third has been implicated in recruiting cellular protein Hsc70 to VFs (6,7,9,10,12,26,27). To examine the impact of the introduced TC-NS mutations, we cotransfected cells with each pTC-NS mutant or wild-type pT7-M3 along with plasmids expressing each of the other six virus proteins individually.…”
Section: Construction Of Plasmids Expressing the Tc Tag From Within Tmentioning
confidence: 99%
See 3 more Smart Citations